Post-processing algorithm of a five-axis machine tool with dual rotary tables based on the TCS method - Yu, Dao-Yang; Ding, Zhi (International journal of advanced manufacturing technology, 2019)
In order to solve the problem of post-processing of a five-axis machine tool with dual rotary tables from workpiece coordinate system to machine tool coordinate system, the paper proposes a solution method namely Two Circle Spherical method (referred to as TCS); the method provides explicit physical geometric meanings for rotation angles of a five-axis machine tool. It is suitable for the post-processing of a five-axis machine tool. The integral impeller was taken as a post-processing case, and the correctness and efficiency of the TCS post-processing algorithm are verified by case calculation, Vericut software simulation, and the actual numerical control (NC) machining experiments; compared with the traditional post-processing algorithm, the superiority of TCS algorithm is verified.